Designing the User Interface for the Virtual Tour Selayar System using Figma - Mustika, Nur; Mirfan, Mirfan; Abdul Kadir Parewe, Andi Maulidinnawati; Layuk, Tika Tandi (Brilliance: Research of Artificial Intelligence, 2024)
This study aims to design the user interface for the Virtual Tour Selayar system using the Figma application. The system is expected to provide an interactive and informative virtual tour experience for users who wish to explore the beauty of Selayar Regency digitally. The design process employs the Design Thinking method, which consists of five main stages: understanding user needs (Empathy), defining the problem to be solved (Define), generating various ideas for potential solutions (Ideate), creating a simple version or initial model (Prototype), and testing the prototype (Tes). The Empathy stage involves observations and interviews to understand users' desires and needs concerning the virtual tour system. Next, the Define stage formulates the primary problem that the system needs to address. In the Ideate stage, various interface ideas and concepts are generated through brainstorming sessions. Subsequently, the Prototype stage produces the initial version of the interface, developed in both low fidelity and high fidelity forms using Figma. The final stage, Testing, is conducted by involving actual users to test the created prototypes. Feedback obtained from users is utilized to refine the interface, ensuring it aligns with their expectations and needs. The outcome of this research is a user interface prototype that has been tested and refined based on feedback, which is anticipated to enhance the user experience when using the Virtual Tour Selayar system effectively and satisfactorily.